Processamento e transformações de fase em ligas para armazenagem de hidrogênio processadas por moagem reativa - Santos, Sydney Ferreira (2004)
In the present work, the phase transformations in metallic materials processed by reactive milling were investigated. The as-milled samples were characterized by X-ray diffraction, transmission and scanning electron microscopy, X-ray dispersive energy spectrometry, differential scanning calorimetry and hydrogen content determination. The effect of the processing parameters on the structure, morphology, hydrogenation and contamination content were analyzed. The processed materials were a Ti33-Cr36-V31 alloy and the elemental powder mixtures Mg-50Ni and Nb-28Mg (compositions in at. %). For the Ti-Cr-V alloy, reactive milling induces the disproportionation of the original BCC solid solution phase resulting in a material composed by a mixture of vanadium hydride, hexagonal Laves phase and V-poor BCC solid solution. For the Mg-50Ni, it was observed the a higher energy mill aids the chemical and morphological homogeneity of the powders. It was also observed that initial hydrogen pressure and milling times affect both hydrogenation and phase formations. For higher times (96h) and pressures (2,0MPa of H2) of milling, it were observed evidences of a Mg-Ni-H phase disproportionation. Finally, the reactive milling of the Nb-28Mg mixture shows the catalytic effect of the Mg on the hydrogenation of this nanocomposite. After 48h milling, the Nb of the nanocomposite were almost all transformed in NbH2 and absorbed 95% of its theoretical hydrogen storage capacity. For pure Nb, processed by the same way, the phase formed was NbH and the metal absorbed only 33% of its theoretical hydrogen storage.